MEMBANGUN PERADABAN BANGSA: PERSPEKTIF SOSIOLOGI AGAMA - Ida Bagus Gde Yudha Triguna (Pascasarjana Universitas Hindu Indonesia, 2017)
Civilization as a representation of the moral commitment of goodness to its citizens [singular and plural] is then used as a reference in the concept of living together. Meanwhile, It is also the source of appreciation, creativity, and expressing feelings. As a valuable moral commitment, it re- quires its adherents to nurture, preserve, and interpret it in the best way according to their meth- odology. The number of ways available to interpret the value have opened up the possibility of po- larization of meaning, so it may open the possibility of bias and differences in the interpretation of a value, moreover, if external factors have contributed to the polarization of how to interpret the value.